Zad 1 Doprowadź wyrażeniua do prostszej postaci:

a. 2x+(2x-y)-(x+2y)+(-2x-y)
b. 2x-(-5x+2y-z)+(-x+y+2z)
(2a+3b)+(-3a+b+2)-(-4a-b-3)

Zad 2 Wstaw odpowiednią liczbę w miejsce ?

a. ? razy (x-5)=3x - 15
b. ? raazy (-2a+3b-1)=8a-12b+4
c. ( 4-6x+8y)razy ? = 2-3x+4y
d. ( 8a-20b-4) razy ? = -2a+5b+1

1

Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-22T15:10:46+01:00
1.
a. 2x+(2x-y)-(x+2y)+(-2x-y) = 2x+2x-y-x-2y-2x-y = x-4y

b. 2x-(-5x+2y-z)+(-x+y+2z) = 2x+5x-2y+z-x+y+2z = 6x-y+3z

c.(2a+3b)+(-3a+b+2)-(-4a-b-3) = 2a+3b-3a+b+2+4a+b+3 = 3a+5b+5

2.
a. 3 * (x-5) = 3x - 15

b. -4 * (-2a+3b-1) = 8a-12b+4

c. ( 4-6x+8y) * ½ = 2-3x+4y

d. ( 8a-20b-4) * (-¼) = -2a+5b+1
1 5 1